A new approach to testing potential leaching toxicity of fouling release coatings (FRCs). (October 2018) - Piazza, Veronica; Gambardella, Chiara; Garaventa, Francesca; Massanisso, Paolo; Chiavarini, Salvatore; Faimali, Marco
Abstract: Fouling release coatings (FRCs) are today the main environment-friendly alternative to traditional self-polishing coatings, that continuously release biocides and/or heavy metals into water. FRCs are available on the market as environmentally friendly AF paints and most of them do not contain bioactive agents, however no complete and reliable assessment of their environmental impact has yet been carried out. Only few literature data proving their AF efficacy combined with a demonstrated lack of toxicological effects are available. Ecotoxicological bioassays are commonly used to predict the potential environmental impact of traditional AF paints. Standardized methodologies to obtain leaching products from biocide-based paints are available, while few studies propose experimental methods to assess the potential effects of biocide-free FRCs leachates on non-target organisms. The aim of this work is to propose an experimental protocol to obtain leaching products from biocide-free FRCs in order to evaluate the potential release of substances having toxic effects, by means of an ecotoxicological bioassay. Two ecotoxicological end-points with different sensitivity levels were considered (multi-end-point approach). Five silicone-based commercial coatings were used: their leaching products were collected after different immersion times following the developed experimental method and then two ecotoxicological end-points were evaluated on II stage nauplii of the crustacean Amphibalanus amphitrite as model organism. Moreover, chemical analyses were performed on leachates collected after each immersion time, focusing on the presence of metals in leaching products. From the results obtained from the bioassay, even if not indicative of the real environmental impact of FRCs, a release of toxic substances was observed from tested coatings during early immersion stages, likely to affect the exposed model organism. The potential leaching toxicity of the five tested products was compared. No clear correspondence could be identified between the concentrations of metals detected in leachates and the obtained ecotoxicological data, thus suggesting that other active components might be released by FRCs responsible for the toxic effects pointed out on A. amphitrite larvae. Highlights: An experimental protocol to obtain leaching products from FRCs is proposed. Bioassays and chemical analysis were performed on FRCs leachates collected at different ageing times. A clear and direct correlation between chemical and ecotoxicological data was not found. Developed method proved to be valid to highlight active components release from FRCs.